Analysis of Local Wisdom (Ethnobiology) in Mulyoharjo Village as a Source of Biology Learning in High School - Bayu Anshor Mursalin; Ambar Indriyani; Anggun Fransiska (ISEJ : Indonesian Science Education Journal, 2025)
Biology education in the modern era demands a contextual and relevant approach to students' lives, yet it remains dominated by theoretical textbook usage. This study aims to analyze the forms of local wisdom (ethnobiology) in Mulyoharjo Village and examine its potential as a biology learning source for senior high schools. This research used a descriptive qualitative method with ethnobiological and ethnographic approaches. Data were collected through field observations, semi-structured interviews with community leaders and traditional medicine practitioners, and documentation. Data analysis followed the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing. The results showed that the community of Mulyoharjo Village possesses rich local wisdom in utilizing various flora as traditional medicine, such as turmeric (Curcuma longa), betel (Piper betle), bitter grape (Tinospora crispa), and cat's whiskers (Orthosiphon aristatus). These utilization practices reflect a harmonious and sustainable reciprocal relationship between humans and the environment. These ethnobiological findings have strong scientific relevance to the Phase E/F high school biology curriculum, particularly in the topics of Biodiversity, Classification of Living Things, and Ecosystems. The study concludes that the local wisdom of Mulyoharjo Village has significant potential to be integrated as a contextual biology learning source to enhance students' environmental literacy and cultural awareness.